MILLEU THERAPY DENGAN SENI KREASI MUSIK TERHADAP KESEPIAN LANSIA SAAT PANDEMI COVID-19 - Ermilda Ermilda; Linda Widyastuti; Siti Nura'eni; Sarah Faulia Azhara (NHM PRESS, 2022)
Loneliness in the elderly is seen as unique because it has an impact on complex health problems. To date, there have been no studies of lonely elderly people during a pandemic. The Milleu Therapy intervention in the art of music (singing) can be used as an alternative to reduce the loneliness of the elderly during a pandemic. One of the advantages of this musical art creation therapy is to develop self-esteem, increase the ability to relate to others, foster an attitude of trust in others, as well as positive change and prepare oneself to return to society by channeling the creativity of the elderly by singing in pandemic situations in the elderly and can cooperate with each other. The purpose of this study was to analyze the effect of milieu therapy in the creation of music on the reduction of loneliness in the elderly during the COVID-19 pandemic. This study used a pre-experimental one-group pre-posttest design. The population in this study used a purposive sampling technique. The results of the Wilcoxon Sign Rank Test statistical test showed an effect of the musical art creation method (singing) on the decrease in the loneliness of the elderly.